Description of a new species of Penicillate Millipede from the genus Monographis (Diplopoda: Polyxenidae) found in Vietnam - Huynh, Cuong; Veenstra, Anneke A. (Zootaxa, 2015)
A new species of penicillate millipede, from genus Monographis (Diplopoda: Polyxenidae), was collected from Trang Bom and Dinh Quan, within the Dong Nai province, southern Vietnam. Taxonomic characteristics of the genus Monographis Attems, 1907, were used to formally describe this new species. Sensilla of the 6th antennal article and claw structures of Monographis dongnaiensis were compared with those of M. tamoyoensis, M. yunnanensis and M. queenslandicus. Genomic DNA of M. dongnaiensis was compared with the DNA of other species within the genus Monographis. Monographis dongnaiensis is confirmed as the ninth member of the genus Monographis and named Monographis dongnaiensis after the collection site Dong Nai province in Vietnam.